PENAFSIRAN SURAT AN-NISA' AYAT 34 TENTANG KEPIMPINAN DALAM AL-QURAN - Makmur Jaya (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2020)
This study aims to determine the theory used by Ibn 'Asyur in interpreting Qs. An-Nisa 'verse 34, as well as describing Ibn' Asyur's interpretation of Qs. An-Nisa 'verse 34 about leadership in the Alquran. This study uses a qualitative method, the data is sourced from the library (library research). To reveal the contents of Ibn 'Asyur's interpretation of QS. An-Nisa verse 34 seen from the munasabah theory. The results of this study can be concluded that QS. An-Nisa verse 34 discusses the superiority of men to be entitled to be leaders, because Allah has exaggerated their class from some other groups. Certain groups often cut this verse for personal gain as a statement of legitimacy that men have the right to become leaders. However, Ibn 'Asyur's tafsirat-tahrir wa tanwir has explained more broadly with his theory of interpretation, that this statement is not true, because in the next sentence Allah explains the husband's obligations towards his wife or family and the actions of the nusyuz wife. Therefore QS. An-Nisa is not talking about leadership in general, but leadership in this verse speaks to the family circle.